2020
DOI: 10.1039/9781788012904-00146
|View full text |Cite
|
Sign up to set email alerts
|

CHAPTER 6. Poly(phosphorhydrazone) Dendrimers and Other Phosphorus-containing Dendrimers

Abstract: This chapter will focus on the methods of synthesis of phosphorus-containing dendritic architectures, mainly of phosphorhydrazone type, coming from our group, but also on other types of phosphorus dendrimers coming from other laboratories. The different types of cores, branches, and surface functionalities of phosphorhydrazone dendrimers will be displayed. An overview of the field will be given, concerning not only regular dendrimers, but also dendrimers with layered architectures, dendrons, and various types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 142 publications
0
7
0
Order By: Relevance
“…The PPH dendrimers have phosphorus atoms in their structure and are nonpolar molecules. They require polar groups to be attached at the periphery of the molecules to make the dendrimers more water-soluble [ 104 ]. The polyester dendrimers have good biocompatibility and biodegradability, and the in vitro activity tests showed that these dendrimers have significant antibacterial activity and can act synergistically with bioactive peptides [ 105 , 106 ].…”
Section: Advances In Nanosystems For Amps Deliverymentioning
confidence: 99%
“…The PPH dendrimers have phosphorus atoms in their structure and are nonpolar molecules. They require polar groups to be attached at the periphery of the molecules to make the dendrimers more water-soluble [ 104 ]. The polyester dendrimers have good biocompatibility and biodegradability, and the in vitro activity tests showed that these dendrimers have significant antibacterial activity and can act synergistically with bioactive peptides [ 105 , 106 ].…”
Section: Advances In Nanosystems For Amps Deliverymentioning
confidence: 99%
“…For details on their preparation, the reader is referred to excellent books and reviews on the literature [ 28 , 29 , 30 ]. In the biomedical field, the dendritic families which stand out are poly(amino amide) (PAMAM) [ 31 ], poly(propylene imine) (PPI), poly(L-lysine) (PLL) [ 32 ], carbosilane [ 33 ], poly(phosphorhydrazone) (PPH) [ 34 ], and polyester dendrimers [ 35 ] ( Figure 2 ). The biocompatibility, flexibility, and commercial availability are behind their prevalence in this field.…”
Section: Dendrimers: Synthesis Uses and Challenges To Face In Bimentioning
confidence: 99%
“…PPH dendrimers, which can be quantitatively prepared up to generation 12 [ 38 ], present phosphorus atoms throughout the entire dendritic scaffold and have been widely studied for biomedical applications [ 34 ], Figure 2 E. Like carbosilane dendrimers, PPH are also “inorganic dendrimers” with a huge variability in cores, branches, and peripheral groups, and require the attachment of polar groups in the periphery to become water-soluble.…”
Section: Dendrimers: Synthesis Uses and Challenges To Face In Bimentioning
confidence: 99%
“…To date, dendrimers are the only polymeric scaffolds capable of providing these features due to their monodispersity and multivalency, , besides the influence of the branched architecture in drug delivery. , Successful examples, at the preclinical or even clinical stage, have been reported for dendrimers comprising polylysine ( e.g ., VivaGel), poly­(amidoamine) (PAMAM), phosphorous, and bis-MPA-based polyester scaffolds, among others. To expand their usefulness, heterofunctional dendrimers (HFDs) were developed, which contain at least two distinctive functionalities typically attached to the dendritic surface in a statistical, alternating, or block manner, but most often having dormant interiors. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, novel synthetic strategies that can expand the scaffolding window of already established dendrimers and in parallel maintain the intrinsic features of the main building block are logical progressions in dendrimer chemistry. , The new multipurpose HFDs would resemble most of the properties of their parents, e.g ., biocompatibility, degradability, and solubility, while providing increased accessibility and carrying capability of the typically dormant interior. To accomplish this, traditional building blocks must be synthetically revisited and reprogrammed to include orthogonal chemoselective groups that are dormant during the dendrimer growth.…”
Section: Introductionmentioning
confidence: 99%